Mathematical model of orthogonal frequency distribution and multiplexing (OFDM) signals - Gorbenko, I.D.; Zamula, O.A.; Morozov, V.L.; Rodionov, S.V. (Radiotekhnika, 2019)
The problematic issues of building noise immunity systems based on the use of orthogonal frequency division-division (OFDM) signal multiplexing are considered. The description of OFDM signaling technology used in telecommunication and telecommunication systems is given, as well as the analysis of promising technologies that can be used in multi-carrier broadband wireless systems, which have high requirements for information security, noise immunity signal reception, data rate. The main purpose of the publication is a sufficiently detailed discussion of some of the problems associated with the development at the physical level of OFDM systems, obtaining mathematical models of transformations in the implementation of OFDM. Particular attention is paid to the possibility of exchange between the quality characteristics of the communication system and its complexity.